Коммуникация в вербальном тексте, вербальный текст в коммуникации - Галло, Ян (Studia Rossica Posnaniensia, 2019)
The article is dedicated to general issues concerning verbal text and communication and the analysis of the communicative structure of a literary text. In the introduction, the interest to research not only text but also the phenomenon of a more complex character – communication – is expressed. The problem of the text as a part of communication process is also discussed taking into account the verbal means. In the first part, the attention is focused on the verbal text in the aspect of communication. The characteristics of implicit parts of the communication process (an author, code, text, channel, recipient, communicative situation) is presented as well. In the third part, there is the analysis of the specific type of a complex semiotic text – a literary verbal text and its communicative comprehension in both productive and receptive aspects. The connection of the text with textual subjects is studied as well. In the last part of the text, the conclusions of presented problems are drawn.